Effect of reducing insulation thickness to the electrical stress of polymeric materials - 394442 Tan, Geok Boon (Kuala Lumpur : UTM, 1996)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1996